Participación del micelio externo de hongos micorrícico-arbusculares en la formación de agregados estables alagua en suelos de ladera con influencia de cenizas volcánicas - Zarate, LM; Barrios, E.; Sánchez, M.; Caballero, LM (2007)
The response to the application of five inocules of arbuscular mycorrhizal fungi (AMF), Entrophospora colombiana ECLB, Gigaspora margarita-GMRG, Glomus manihotis-LMNH, and live and sterilized mixture of the three AMF species, using both undesinfected (U) and desinfected (D) substrate, seeded or not with Melinis minutiflora Beauv., on the mycorrhizal colonization, on the formation of external mycelium (EM), and on the percentage of water stable aggregates (WSA) of the fractions >2.0, 2.0-0.250, 0.250-0.125 y <0.125 mm, was determined under greenhouse conditions (CIAT, Cali, Colombia). Two-compartments plant pots, 13.5 x 8.0 x 14.0 cm each, communicated by a 60 cm2 central opening covered by a nylon mesh 37?m were used. Substrate came from mixing mountain soil influenced by volcanic ashes (Inceptisol), previously seined with sand. U substrate significantly favored colonization and EM length of the different AMF present in M. minutiflora along the evaluation period. It was found that EM of the AMF associated to M. minutiflora interacting with soil conditions, participated significantly on the formation of WSA >0.250 mm (macro aggregates). However, U substrate stimulated especially WSA fraction >2.0 mm. Results corroborated microorganisms participation on soil structure.